Iceland's Arctic Strategy. Security challenges and opportunities - Jón Ágúst Guðmundsson 1979- (2010)
In recent years there have been great changes in the High North as result of global warming and climate change. This has drawn increased attention towards the region from various global actors, among them the actual Arctic states and international organizations. The Arctic Council is one of the main forums dealing with Arctic affairs. All its members have stated the importance of continuing to work together within the council and behaving according to international law and treaties. UNCLOS and IMO are important in that respect. The Arctic states either have published or are working on publishing their national strategies for the region based on the strategic importance and potential economic benefits the opening of the Arctic can have. Some sabre rattling has been taking place between Arctic states but it is not likely that there will be military conflict in the region over unresolved disputes. International organizations like NATO and the EU have shown interest in greater involvement in the region. The Arctic states do not have a common policy on whether to open up the Arctic for the organizations or not. Russia is taking a harsh stand against any interference by them in what it describes as a priority Russian zone of interest. Iceland has published its Arctic strategy. The key to Iceland’s strategy is continued cooperation with the Arctic Council. Therefore it is important to avoid any behaviour that gives the five Arctic literal states grounds to meet outside the Council's forum. The strategy gives a good indication on what Iceland wants but not on the way it wants to go to achieve that goal. Work needs to be done within the political elite and administration and with the help of scholars to define the security needs of Iceland. A complete study of the security needs of the state is needed which covers both civil and military security. The tendency of the political elite to avoid touching on security concepts must stop so that there can be logical debate on the matter. That is the prerequisite for an active, ...